Water-soluble dispersing agent as well as preparation method and application thereof
By using polyacrylic acid and polyacrylonitrile block polymers as water-soluble dispersants, the problem of poor viscosity and fluidity of water-based carbon nanotube conductive paste during storage is solved, and the stability and efficiency of the conductive paste are achieved. use.
Patent Information
- Application Number
- CN202411453484.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-02-11
AI Technical Summary
The existing water-based carbon nanotube conductive paste is prone to gel during storage, with large viscosity rebound and poor fluidity and dispersion, resulting in complex usage processes and harsh storage conditions.
A polymer is used as a water-soluble dispersant, including polyacrylic acid and polyacrylonitrile blocks, and the solubility and viscosity in water are made by a specific preparation method, and is used to prepare conductive pastes.
It improves the flowability and stability of the conductive paste, reduces viscosity and resistivity, simplifies the use process and storage conditions, and meets the demand for negative electrode paste of lithium-ion batteries.
Smart Images

Figure CN119409912A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of lithium ion batteries, and in particular to a water-soluble dispersant and a preparation method and application thereof. Background Art
[0002] Carbon nanotube (CNT) conductive agent has a high aspect ratio and flexibility. When added to the negative electrode, it can serve as a buffer zone for the volume expansion of the negative electrode material, thereby alleviating the volume expansion of the negative electrode material. Even if the volume of the negative electrode particles expands and cracks appear, the carbon nanotubes can maintain a persistent conductive network channel when the particles expand or even break, thereby maintaining the capacity of the electrode material. CNT uses polyvinyl pyrrolidone as a dispersant in an organic solvent. CNT agglomerates can be broken up by physical methods such as stirring, grinding, and ultrasound, and CNT can be prepared into various stable and dispersed slurries, which are finally used in the form of slurries in lithium-ion battery production. However, in aqueous conductive slurries, the longer the one-dimensional carbon nanomaterial is, the easier it is for them to entangle with each other and the more difficult it is to disperse. At present, polyvinyl pyrrolidone or sodium carboxymethyl cellulose is generally used as a dispersant in water-based carbon nanotube conductive slurry. The conductive slurry of carbon nanotubes dispersed with polyvinyl pyrrolidone or sodium carboxymethyl cellulose as a dispersant is prone to gelation during storage, has a large viscosity rebound, and has poor fluidity and dispersibility. Mechanical stirring is generally required before use, resulting in complex use processes and harsh storage conditions for the water-based carbon nanotube conductive slurry. Summary of the invention
[0003] In order to overcome the problems existing in the prior art, one of the objects of the present invention is to provide a water-soluble dispersant.
[0004] A second object of the present invention is to provide a method for preparing a water-soluble dispersant.
[0005] A third object of the present invention is to provide a conductive paste.
[0006] A fourth object of the present invention is to provide a negative electrode slurry for a lithium ion battery.
[0007] A fifth object of the present invention is to provide application of the above-mentioned water-soluble dispersant and / or conductive slurry in the field of batteries.
[0008] In order to achieve the above object, the technical solution adopted by the present invention is:
[0009] The first aspect of the present invention provides a water-soluble dispersant, comprising a polymer represented by formula (I):
[0010]
[0011] in,
[0012] R +Selected from H + 、Na + , Li + , K + ;
[0013] a is a natural number selected from 20 to 100;
[0014] b is a natural number selected from 5 to 50.
[0015] Preferably, a is greater than b.
[0016] Preferably, the relative molecular mass of the polymer is 2600-15000.
[0017] Preferably, the solubility of the polymer in water at 25° C. is not less than 35 g / 100 g.
[0018] Preferably, the viscosity of the aqueous solution of the polymer with a mass percentage of 40% measured at a temperature of 25° C. is 15 to 300 cp. The viscosity of the aqueous solution of the polymer with a mass percentage of 40% measured at 25° C. is ≤300 cp, which has a low viscosity, is convenient to use, has good leveling properties, and does not cause gelation.
[0019] Preferably, the water-soluble dispersant also includes a dispersant aid.
[0020] Preferably, the dispersant comprises polyvinyl pyrrolidone.
[0021] Preferably, the mass ratio of the dispersant to the polymer is 1:(0.5-3).
[0022] The second aspect of the present invention provides a method for preparing the water-soluble dispersant according to the first aspect of the present invention, comprising the following steps:
[0023] S1: mixing acrylic acid, a chain transfer agent and an initiator to carry out polymerization reaction to obtain a prepolymer;
[0024] S2: The prepolymer, acrylonitrile and initiator are mixed to carry out polymerization reaction, and then mixed with water or alkaline solution to purify to obtain the water-soluble dispersant.
[0025] Preferably, the step S1 is: mixing a chain transfer agent (RAFT), acrylic acid (AA), an initiator and an organic solvent A, and then performing a polymerization reaction under the protection of an inert gas to obtain a prepolymer.
[0026] Preferably, the chain transfer agent is selected from The role of the chain transfer agent in the present invention is to make the polymer have a higher regularity and control the molecular weight of the polymer.
[0027] Preferably, the organic solvent A in step S1 is at least one selected from N,N-dimethylformamide, 1,4-dioxane, dimethyl sulfoxide, and N-methylpyrrolidone.
[0028] Preferably, the polymerization reaction temperature in step S1 is 50-80°C.
[0029] Preferably, the polymerization reaction time in step S1 is 2 to 12 hours.
[0030] Preferably, in step S1 and / or step S2, the initiator is selected from at least one of azobisisobutyronitrile, azobisisoheptanenitrile, 1,1'-azo(cyanocyclohexane), 4,4'-azobis(4-cyanovaleric acid), and dibenzoyl peroxide.
[0031] Preferably, the step S2 is: cooling the prepolymer, then mixing it with acrylonitrile, an initiator and an organic solvent B and performing a polymerization reaction under the protection of an inert gas, removing the organic solvent B, and then mixing it with water or an alkali solution for purification to obtain the water-soluble dispersant.
[0032] Preferably, the cooling step is to reduce the temperature of the prepolymer to 20-40°C.
[0033] Preferably, the polymerization reaction temperature in step S2 is 65-95°C.
[0034] Preferably, the polymerization reaction time in step S2 is 2 to 24 hours.
[0035] Preferably, the organic solvent B is selected from at least one of N,N-dimethylformamide, 1,4-dioxane, dimethyl sulfoxide and N-methylpyrrolidone.
[0036] Preferably, the alkali solution is selected from at least one of sodium hydroxide solution, sodium carbonate solution, potassium hydroxide solution, potassium carbonate solution, lithium hydroxide solution and lithium carbonate solution.
[0037] Preferably, the inert gas is selected from at least one of argon, nitrogen and xenon.
[0038] The third aspect of the present invention provides a conductive paste, comprising a conductive agent and the water-soluble dispersant described in the first aspect of the present invention. The water-soluble dispersant in the present invention can reduce the viscosity of the conductive paste, increase the solid content of the conductive paste and the negative electrode paste, and reduce energy consumption in the conductive paste; on the other hand, it can improve the leveling of the negative electrode paste, improve the coating stability and coating efficiency. In addition, the excellent dispersibility of the water-soluble dispersant can help achieve the processing requirements of high solid content, high compaction, and high surface density negative electrode sheets.
[0039] Preferably, the conductive paste comprises the following components in parts by weight: 0.2 to 10 parts of a water-soluble dispersant, 0.4 to 5 parts of a conductive agent, and 85 to 105 parts of a solvent.
[0040] Preferably, the solvent comprises water.
[0041] Preferably, the conductive agent is selected from at least one of multi-walled carbon nanotubes (tube diameter 8-40 nm), oligo-walled carbon nanotubes (tube diameter 4-7 nm), and single-walled carbon nanotubes (tube diameter 1-3 nm).
[0042] Preferably, the conductive paste is prepared by mixing and grinding a dispersant, a conductive agent and a solvent.
[0043] Preferably, the grinding rotation speed is 1000-10000 rpm.
[0044] The fourth aspect of the present invention provides a negative electrode slurry for a lithium ion battery, comprising the conductive slurry described in the third aspect of the present invention.
[0045] Preferably, the negative electrode slurry for lithium ion battery comprises the following components in parts by weight: 0.1 to 3 parts of conductive slurry, 85 to 95 parts of active material, 1 to 5 parts of binder, and 30 to 85 parts of solvent.
[0046] Preferably, the active material is selected from at least one of artificial graphite, natural graphite, silicon carbon, silicon oxygen, and hard carbon.
[0047] Preferably, the binder is selected from at least one of sodium carboxymethyl cellulose, styrene-butadiene rubber, polyacrylic acid and polyacrylate.
[0048] Preferably, the solvent comprises water.
[0049] Preferably, the negative electrode slurry is prepared by mixing various raw materials and then grinding them; further preferably, the negative electrode slurry is prepared by mixing part of the binder and the solvent, and then mixing them with the conductive slurry and the active material in sequence, and then mixing them with the remaining binder to prepare the negative electrode slurry.
[0050] Preferably, part of the binder is sodium carboxymethyl cellulose.
[0051] Preferably, the remaining binder is styrene-butadiene rubber.
[0052] The fifth aspect of the present invention provides the use of the water-soluble dispersant described in the first aspect of the present invention and / or the conductive paste described in the third aspect of the present invention in the field of batteries.
[0053] The beneficial effects of the present invention are as follows: the polyacrylic acid / polyacrylate chain segment in the water-soluble dispersant of the present invention improves the solubility of the polymer in water, so that the water-soluble dispersant has excellent water solubility, and the polyacrylonitrile chain segment improves the adsorption effect of the water-soluble dispersant on the conductive agent, so that the conductive agent can be stably and evenly dispersed in water, avoiding the occurrence of agglomeration and entanglement.
[0054] The conductive paste in the present invention has excellent viscosity, fineness stability, excellent fluidity and leveling performance, no precipitation and stratification occurs after storage for 48 hours, the viscosity change of the conductive paste at room temperature for 7 days is ≤2000cp, the particle size change of the conductive paste at room temperature for 7 days is ≤1μm, the fluidity of the conductive paste does not deteriorate after 7 days of standing, and the viscosity change of the conductive paste at high temperature for 7 days is ≤2000cp; in addition, the water-soluble dispersant in the conductive paste of the present invention can stably disperse the conductive agent, improve the stability of the conductive paste, further promote the construction of a three-dimensional conductive network, and reduce the resistivity. BRIEF DESCRIPTION OF THE DRAWINGS
[0055] Figure 1 This is a physical picture of the carbon nanotube water-soluble dispersant in Example 1.
[0056] Figure 2 This is a physical picture of the carbon nanotube water-soluble dispersant in Example 2.
[0057] Figure 3 This is a physical picture of the carbon nanotube water-soluble dispersant in Example 3.
[0058] Figure 4 This is a physical picture of the conductive paste in Example 4.
[0059] Figure 5 This is a physical picture of the conductive paste in Example 7.
[0060] Figure 6 This is a physical picture of the conductive paste in Example 8.
[0061] Figure 7 This is a physical picture of the conductive paste in Comparative Example 1.
[0062] Figure 8 This is a physical picture of the conductive paste in Comparative Example 2.
[0063] Fig. 9 This is a scraper fineness test chart of the conductive paste in Example 6.
[0064] Fig.10 This is a scraper fineness test chart of the conductive paste in Example 7.
[0065] Fig.11 This is a scraper fineness test chart of the conductive paste in Example 8.
[0066] Fig.12 This is a scanning electron microscope image of a film formed by the conductive paste blade in Example 6.
[0067] Fig.13 This is a scanning electron microscope image of a film formed by the conductive paste blade in Example 7.
[0068] Fig.14 This is a scanning electron microscope image of a film formed by the conductive paste blade in Example 8.
[0069] Fig.15 This is a scraper fineness test diagram of the negative electrode slurry in Example 10.
[0070] Fig.16 This is a scraper fineness test diagram of the negative electrode slurry in Example 11.
[0071] Fig.17 This is a scraper fineness test diagram of the negative electrode slurry in Example 12.
[0072] Fig.18 : is a scanning electron microscope image of the film formed by the negative electrode slurry scraper in Example 10.
[0073] Fig.19 This is a scanning electron microscope image of the film formed by the negative electrode slurry scraper in Example 11.
[0074] Fig. 20 This is a scanning electron microscope image of the film formed by the negative electrode slurry scraper in Example 12.
[0075] Fig.21 The rheological test data of Examples 6 to 8 and Comparative Examples 1 to 2 are shown.
[0076] Fig. 22 It is a comparison chart of the film resistance of Examples 6 to 8 and Comparative Examples 1 to 2.
[0077] Fig.23 It is the viscosity change curve diagram of Examples 6 to 8 and Comparative Examples 1 to 2. DETAILED DESCRIPTION
[0078] The specific implementation of the present invention is further described in detail below in conjunction with the accompanying drawings and examples, but the implementation and protection of the present invention are not limited thereto. It should be noted that if there are processes that are not particularly described in detail below, they can be implemented or understood by those skilled in the art with reference to the prior art. The reagents or instruments used that do not indicate the manufacturer are all conventional products that can be purchased commercially.
[0079] Example 1
[0080] This example provides a carbon nanotube water-soluble dispersant, which is prepared by the following preparation method, the specific steps are:
[0081] (1) Under nitrogen protection, 2-[(dodecylthiothiocarbonyl)thio]propionic acid (PADTC, 1 mol, 350 g), acrylic acid (AA, 50 mol, 3603 g), azobisisobutyronitrile (AIBN, 0.7 mol, 115 g) and N-methylpyrrolidone (NMP, 6000 mL) were added to a 20 L reactor and reacted at 70 ° C for 6 h to obtain a yellow polymer solution;
[0082] (2) After the yellow polymer solution was cooled to 25°C, acrylonitrile (AN, 20 mol, 1061 g), azobisisobutyronitrile (AIBN, 0.7 mol, 115 g), and N-methylpyrrolidone (NMP, 1500 mL) were added, and the mixture was heated to 75°C again under nitrogen protection for 12 h.
[0083] (3) After N-methylpyrrolidone is recovered by evaporation, the obtained product is dissolved in 7500 mL of pure water and filtered to obtain a 40% by weight water-soluble dispersant solution, which is denoted as PAA(50)-b-PAN(20). The physical diagram is shown in FIG. Figure 1 As shown, the viscosity of the water-soluble dispersant solution at 25° C. is tested using a Brookfield viscometer, and the data after the viscosity stabilizes is read, and the viscosity value is 150 cP.
[0084] The reaction equation is:
[0085]
[0086] Example 2
[0087] This example provides a carbon nanotube water-soluble dispersant, which is prepared by the following preparation method, the specific steps are:
[0088] (1) Under nitrogen protection, 2-[(dodecylthiothiocarbonyl)thio]propionic acid (PADTC, 1 mol, 350 g), acrylic acid (AA, 50 mol, 3603 g), azobisisobutyronitrile (AIBN, 0.7 mol, 115 g) and N-methylpyrrolidone (NMP, 6000 mL) were added to a 20 L reactor and reacted at 70 ° C for 6 h to obtain a yellow polymer solution;
[0089] (2) After the yellow polymer solution was cooled to 25°C, acrylonitrile (AN, 20 mol, 1061 g), azobisisobutyronitrile (AIBN, 0.7 mol, 115 g), and N-methylpyrrolidone (NMP, 1500 mL) were added, and the solution was heated to 75°C under nitrogen protection and reacted for 12 h.
[0090] (3) After N-methylpyrrolidone is recovered by evaporation, the obtained product is added into 10200 g of sodium hydroxide aqueous solution (the mass percentage of NaOH in the sodium hydroxide aqueous solution is 20 wt.%) to dissolve the obtained product. After filtration, a 40 wt.% water-soluble carbon nanotube dispersant solution of this example is obtained, which is denoted as PANa(50)-b-PAN(20). The actual picture is shown in FIG. Figure 2 As shown, the viscosity of the water-soluble dispersant solution at 25° C. was tested using a Brookfield viscometer, and the data after the viscosity stabilized was read, and the viscosity value was 210 cP.
[0091] The reaction equation is:
[0092]
[0093] Example 3
[0094] This example provides a carbon nanotube water-soluble dispersant, which is prepared by the following preparation method, the specific steps are:
[0095] (1) Under nitrogen protection, 2-[(dodecylthiothiocarbonyl)thio]propionic acid (PADTC, 1 mol, 350 g), acrylic acid (AA, 50 mol, 3603 g), azobisisobutyronitrile (AIBN, 0.7 mol, 115 g) and N-methylpyrrolidone (NMP, 6000 mL) were added to a 20 L reactor and reacted at 70 ° C for 6 h to obtain a yellow polymer solution;
[0096] (2) After the yellow polymer solution was cooled to 25°C, acrylonitrile (AN, 20 mol, 1061 g), azobisisobutyronitrile (AIBN, 0.7 mol, 115 g), and N-methylpyrrolidone (NMP, 1500 mL) were added, and the solution was heated to 75°C under nitrogen protection and reacted for 12 h.
[0097] (3) After evaporating and recovering N-methylpyrrolidone, 7000 g of lithium hydroxide aqueous solution (17 wt.% LiOH) was added to the obtained product to dissolve the obtained product. After filtering, a 40% by weight carbon nanotube water-soluble dispersant solution in this example was obtained, which was recorded as PALi(50)-b-PAN(20). The actual picture is shown in FIG. Figure 3 As shown, the viscosity of the water-soluble dispersant solution at 25° C. is tested using a Brookfield viscometer, and the data after the viscosity stabilizes is read, and the viscosity value is 200 cP.
[0098] The reaction equation is:
[0099]
[0100] The solubility of the dispersants in Examples 1 to 3 of the present invention in water at 25° C. was tested to be no less than 35 g / 100 g.
[0101] Example 4
[0102] This example provides a conductive paste, which is prepared by the following preparation method, the specific steps are:
[0103] Take 30g of the PAA(50)-b-PAN(20) aqueous solution in Example 1, 12g of polyvinyl pyrrolidone, 100g of carbon nanotubes GRF-C3110, and 1858g of pure water and put them in a sand mill. Adjust the sand mill speed to 2500rpm. After grinding for 3h, collect the conductive slurry, which is recorded as WS-4-PAA(50)-b-PAN(20).
[0104] The actual picture of the conductive paste in this example is as follows Figure 4 As shown, the test found that the mass percentage of CNT in the conductive paste of this example was 5%, and the mass percentage of PAA(50)-b-PAN(20) was 1.2%.
[0105] Example 5
[0106] This example provides a conductive paste, which is prepared by the following preparation method, the specific steps are:
[0107] Take 30g of the PAA(50)-b-PAN(20) aqueous solution of Example 1, 12g of polyvinyl pyrrolidone, 60g of carbon nanotubes GRF-C4000, and 1898g of pure water and put them in a sand mill. Adjust the sand mill speed to 2500rpm / min. After grinding for 3h, collect the conductive slurry, which is recorded as WS-6-PAA(50)-b-PAN(20).
[0108] The test results show that the mass percentage of CNT in the conductive paste of this example is 3%, and the mass percentage of PAA(50)-b-PAN(20) is 1.2%.
[0109] Example 6
[0110] This example provides a conductive paste, which is prepared by the following preparation method, the specific steps are:
[0111] Take 15g of the PAA(50)-b-PAN(20) aqueous solution of Example 1, 6g of polyvinyl pyrrolidone, 8g of Griffin SWCNT, and 1971g of pure water and put them in a sand mill. Adjust the sand mill speed to 2500rpm / min. After grinding for 3h, collect the conductive slurry, which is recorded as WS-10-PAA(50)-b-PAN(20).
[0112] The test results show that the mass percentage of CNT in the conductive paste of this example is 0.4%, and the mass percentage of PAA(50)-b-PAN(20) is 0.6%.
[0113] Example 7
[0114] The conductive paste in this example is different from that in Example 6 only in that: in this example, the PANa(50)-b-PAN(20) aqueous solution of Example 2 is used in place of the PAA(50)-b-PAN(20) aqueous solution of Example 1, and the resulting conductive paste is recorded as WS-10-PANa(50)-b-PAN(20).
[0115] The actual picture of the conductive paste in this example is as follows Figure 5 As shown, it was found through testing that the mass percentage of CNT in the conductive paste of this example was 0.4%, and the mass percentage of PANa(50)-b-PAN(20) was 0.6%.
[0116] Example 8
[0117] The conductive paste in this example is different from that in Example 6 only in that the PALi(50)-b-PAN(20) aqueous solution in Example 3 is used in place of the PAA(50)-b-PAN(20) aqueous solution in Example 1, and the resulting conductive paste is designated as WS-10-PALi(50)-b-PAN(20).
[0118] The actual picture of the conductive paste in this example is as follows Figure 6 As shown, it was found through testing that the mass percentage of CNT in the conductive paste of this example was 0.4%, and the mass percentage of PALi(50)-b-PAN(20) was 0.6%.
[0119] Example 9
[0120] This example provides a conductive paste, which is prepared by the following preparation method, the specific steps are:
[0121] Take 25g of the PAA(50)-b-PAN(20) aqueous solution of Example 1, 10g of polyvinyl pyrrolidone, 20g of Griffin SWCNT, and 1945g of pure water and put them in a sand mill. Adjust the sand mill speed to 2500rpm / min. After grinding for 3h, collect the conductive slurry, which is recorded as Max-PAA(50)-b-PAN(20).
[0122] It was found through testing that the mass percentage of CNT in the conductive paste of this example was 1.0%, and the mass percentage of PAA(50)-b-PAN(20) was 1.0%.
[0123] When CMC is used as a dispersant to disperse CNTs in the conductive paste prepared, the maximum mass percentage of CNTs that can be dispersed is 0.4%. When PVP is used as a dispersant to disperse CNTs in the conductive paste prepared, the maximum mass percentage of CNTs that can be dispersed is 0.4%. In Example 9, when PAA(50)-b-PAN(20) is used as a dispersant to disperse CNTs in the conductive paste prepared, the mass percentage of CNTs is 1%.
[0124] Example 10
[0125] This example provides a negative electrode slurry for a lithium ion battery, which is prepared by the following preparation method, and the specific steps are:
[0126] Commercially available silicon dioxide negative electrode active material, sodium carboxymethyl cellulose, styrene-butadiene rubber, and conductive slurry were mixed in a mass ratio of 100:1:1.4:0.3, and water was added to make the solid content of the negative electrode slurry 50-60%, thereby preparing the negative electrode slurry for lithium ion battery in this example, which was recorded as SiO-WS-10-PAA(50)-b-PAN(20) negative electrode slurry. The conductive slurry was the conductive slurry in Example 6.
[0127] After the SiO-WS-10-PAA(50)-b-PAN(20) negative electrode slurry in this example was coated on a PET film, the electrode sheet resistance was tested using a four-probe test method and was found to be 6.5Ω·cm. After being coated on a copper foil, the electrode sheet resistance was tested using a two-probe test method and was found to be 31.5Ω·cm.
[0128] Embodiment 11
[0129] The only difference between the negative electrode slurry for lithium-ion batteries in this example and that in Example 10 is that this example uses an equal amount of WS-10-PANa(50)-b-PAN(20) aqueous conductive slurry in Example 7 to replace the WS-10-PAA(50)-b-PAN(20) aqueous conductive slurry in Example 6, and the resulting negative electrode slurry is recorded as SiO-WS-10-PANa(50)-b-PAN(20) negative electrode slurry.
[0130] After the SiO-WS-10-PANa(50)-b-PAN(20) negative electrode slurry in this example was coated on a PET film, the electrode sheet resistance tested by a four-probe test method was 7.1Ω·cm. After being coated on a copper foil and tested by a two-probe test method, the electrode sheet resistance was 30.8Ω·cm.
[0131] Example 12
[0132] The only difference between the negative electrode slurry for lithium-ion batteries in this example and that in Example 10 is that this example uses an equal amount of WS-10-PALi(50)-b-PAN(20) aqueous conductive slurry in Example 8 to replace the WS-10-PAA(50)-b-PAN(20) aqueous conductive slurry in Example 6, and the resulting negative electrode slurry is recorded as SiO-WS-10-PALi(50)-b-PAN(20) negative electrode slurry.
[0133] After the SiO-WS-10-PALi(50)-b-PAN(20) negative electrode slurry in this example was coated on a PET film, the electrode sheet resistance tested by a four-probe test method was 7.0Ω·cm. After being coated on a copper foil and tested by a two-probe test method, the electrode sheet resistance was 30.6Ω·cm.
[0134] Comparative Example 1
[0135] The conductive paste in this example is different from that in Example 6 only in that this example uses commercially available PVP-K30 (polyvinyl pyrrolidone with a molecular weight of 44,000-54,000 Da) of equal mass to replace the PAA (50) -b-PAN (20) aqueous solution in Example 1, and the resulting conductive paste is recorded as WS-10-PVP.
[0136] The actual picture of the conductive paste in this example is as follows Figure 7 As shown, it was found through testing that the mass percentage of CNT in the conductive paste of this example was 0.4%, and the mass percentage of PVP-K30 dispersant was 0.6%.
[0137] Comparative Example 2
[0138] The difference between the conductive paste in this example and that in comparative example 1 is that this example uses commercially available CMC of equal quality to replace the commercially available PVP-K30 in comparative example 1, and the obtained conductive paste is recorded as WS-10-CMC.
[0139] The actual picture of the conductive paste in this example is as follows Figure 8 As shown, it is found through testing that the mass percentage of CNT in the conductive paste of this example is 0.4%, and the mass percentage of PVP-K30 dispersant is 0.6%.
[0140] Comparative Example 3
[0141] The only difference between the negative electrode slurry for lithium ion batteries in this example and Example 10 is that this example uses the WS-10-PVP aqueous conductive slurry of Comparative Example 1 instead of the WS-10-PAA (50) -b-PAN (20) aqueous conductive slurry of Example 6, and the obtained negative electrode slurry is recorded as SiO-WS-10-PVP negative electrode slurry.
[0142] After the SiO-WS-10-PVP negative electrode slurry was coated on the PET film, the electrode sheet resistance tested by the four-probe test method was 24.5Ω·cm. After being coated on the copper foil and tested by the two-probe test method, the electrode sheet resistance was 136.7Ω·cm.
[0143] Comparative Example 4
[0144] The only difference between the negative electrode slurry for lithium ion batteries in this example and Example 10 is that this example uses the WS-10-CMC aqueous conductive slurry of Comparative Example 2 in place of the WS-10-PAA(50)-b-PAN(20) aqueous conductive slurry of Example 6, and the resulting negative electrode slurry is recorded as SiO-WS-10-CMC negative electrode slurry.
[0145] After the SiO-WS-10-CMC negative electrode slurry was coated on the PET film, the electrode sheet resistance tested by the four-probe test method was 21.6Ω·cm. After being coated on the copper foil and tested by the two-probe test method, the electrode sheet resistance was 119.4Ω·cm.
[0146] Performance Testing
[0147] (1) Viscosity and fluidity test
[0148] The viscosity and fluidity of the conductive pastes in Examples 4 to 9 and Comparative Examples 1 to 2 were tested respectively, and the specific testing method was as follows:
[0149] Discharge viscosity test method: Take 200 mL of the conductive pastes in Examples 4 to 9 and Comparative Examples 1 to 2 just prepared, respectively, use a Brookfield viscometer to test the viscosity of the conductive pastes at 25° C., and read the data after the viscosity stabilizes.
[0150] Viscosity test method after standing for 7 days: After the conductive pastes in Examples 4 to 9 and Comparative Examples 1 to 2 were left standing for 7 days, the viscosity of the conductive pastes at 25° C. was tested again using a Brookfield viscometer to test the viscosity after standing.
[0151] Fluidity test method: Take 20g of the just-prepared conductive pastes in Examples 4 to 9 and Comparative Examples 1 to 2 and place them in a surface dish to observe whether the conductive paste can level quickly. The fluidity is excellent: the leveling time is <10min; the fluidity is good: 10min≤leveling time≤30min; the fluidity is poor: the leveling time is >30min.
[0152] The viscosity and fluidity data of the conductive pastes in Examples 4 to 9 and Comparative Examples 1 to 2 measured according to the above test method are shown in Table 1.
[0153] Table 1 Conductive slurry viscosity and fluidity test results
[0154]
[0155]
[0156] As can be seen from Table 1, the viscosity of the conductive pastes of Comparative Examples 1 to 2 increases rapidly, and the viscosity increases by ≥3000cp after standing for 7 days, and the fluidity is poor. However, the viscosity of the conductive pastes in Examples 4 to 9 increases by ≤2000cp after standing for 7 days, and the fluidity is excellent. The viscosity change is significantly less than that of Comparative Examples 1 to 2. The reason is that the polyacrylic acid in the polyacrylic acid polyacrylonitrile block polymers in Examples 4 to 9 has strong hydrophilicity and can have extremely high solubility in water solvents. At the same time, the cyano group (C≡N) of polyacrylonitrile has a strong interaction force with the carbon-carbon bond (CC) of carbon nanotubes, and can adsorb carbon nanotubes. Therefore, PAA (a) -b-PAN (b) as a water-soluble dispersant can disperse multi-walled carbon nanotubes, oligo-walled carbon nanotubes, and single-walled carbon nanotubes. Among them, the discharge viscosity of the conductive pastes in Examples 4 to 8 is ≤1000cp, and the viscosity is ≤3000cp after standing for 7 days. Taking the viscosity of 5000 cp within the shelf life as the upper limit and maintaining the fluidity of the slurry as an indicator, the conductive slurries in Examples 4 to 9 of the present invention all meet the use requirements of lithium-ion batteries.
[0157] Depend on Figures 4 to 8 It can be seen that the conductive paste in the present invention has excellent fluidity and can be quickly leveled, while the conductive paste in Comparative Example 1 has slightly poor leveling performance, and the conductive paste in Comparative Example 2 cannot be leveled.
[0158] The conductive pastes in Examples 6 to 8 were subjected to a scraper fineness test, and each sample was tested in two groups in parallel. The specific test diagram is shown in FIG. Figures 9 to 11 As shown by Figures 9 to 11 It can be seen that the conductive pastes in Examples 6 to 8 have excellent scraper fineness. The surface morphology of the film formed by the conductive paste scraper in Examples 6 to 8 was tested using a scanning electron fiber microscope. The specific test results are as follows: Figure 12 to Figure 14 As shown. Figure 12 to Figure 14 It can be seen that the water-soluble dispersant in the present invention can disperse the carbon nanotubes uniformly with good dispersion effect, and no agglomeration of the carbon nanotubes occurs.
[0159] The negative electrode slurry for the lithium-ion batteries in Examples 10 to 12 was subjected to a scraper fineness test. Two groups of each sample were tested in parallel. The specific test diagram is shown in FIG. Figure 15 to Figure 17 As shown by Figure 15 to Figure 17 It can be seen that the negative electrode slurry for lithium ion batteries in Examples 10 to 12 has excellent scraping fineness. The surface morphology of the film formed after the scraping was tested using a scanning electron microscope. The specific test results are as follows: Figure 18 to Figure 20As can be seen from the figure, the carbon nanotubes in the conductive agent of the negative electrode slurry for lithium ion batteries in Examples 10 to 12 can disperse with the silicon oxygen negative electrode active material to build a conductive network. This is also the reason why the four-probe film resistance and two-probe film resistance of the negative electrode slurry for lithium ion batteries in Examples 10 to 12 are both low.
[0160] (2) Cohesion and peel strength test
[0161] The cohesive force and peeling force of the negative electrode slurries in Examples 10 to 12 and Comparative Examples 3 to 4 were tested respectively, and the specific testing method was as follows:
[0162] Cohesion test method: The negative electrode slurries in Examples 10 to 12 and Comparative Examples 3 to 4 were coated on copper foil respectively, dried at 90°C for 30 minutes, and the surface density was controlled to be 98 g / m 2 , compacted 1.7, used 3M single-sided tape to stick one end to the negative electrode sheet, and placed the other end on a tensile testing machine for testing.
[0163] Peel force test method: The negative electrode slurries in Examples 10 to 12 and Comparative Examples 3 to 4 were coated on copper foil respectively, dried at 90°C for 30 minutes, and the surface density was controlled to 98 g / m 2 , compact 1.7, use 3M double-sided tape to stick it to the negative electrode sheet, take another piece of 3M double-sided tape and stick one end to the negative electrode sheet, and place the other end on the tensile machine for testing.
[0164] The cohesive force and peeling force data of the negative electrode slurries in Examples 10 to 12 and Comparative Examples 3 to 4 measured according to the above test method are recorded in Table 2 below.
[0165] Table 2 Cohesion and peeling force test results of negative electrode slurry
[0166] Test Group Sample name Cohesion(N·m) Peel force (N·m) Example 10 SiO-WS-4-PAA(50)-b-PAN(20) 12.2 21.0 Embodiment 11 SiO-WS-6-PANa(50)-b-PAN(20) 11.9 20.5 Example 12 SiO-WS-10-PALi(50)-b-PAN(20) 12.6 21.8 Comparative Example 3 SiO-WS-10-PVP 5.4 9.5 Comparative Example 4 SiO-WS-10-CMC 3.5 7.6
[0167] As shown in Table 2, the conductive paste dispersed by the polyacrylic acid polyacrylonitrile block polymer water-soluble dispersant in Examples 10-12 can greatly improve the cohesion and peeling force of the pole piece. This is because the water-soluble dispersant can better retain the structure of the carbon nanotubes and retain a larger aspect ratio, thereby building a more stable and effective three-dimensional particle structure when the negative electrode slurry is mixed, and enhancing the contact of the particles. This can also be verified from the fact that the pole piece resistance of Examples 10-12 is much smaller than that of Comparative Examples 3-4.
[0168] The rheological data, film resistance and viscosity change data of the conductive pastes in Examples 6 to 8 and Comparative Examples 1 to 2 were tested respectively, and the specific testing methods were as follows:
[0169] Rheological data test method: Take 5 mL of the conductive slurry in Examples 6 to 8 and Comparative Examples 1 to 2 and place it on the rheometer test sample table and test for 1 to 100 seconds.-1 Conductive paste viscosity.
[0170] Membrane resistance test method: prepare the slurry according to the ratio of negative electrode active material: conductive slurry: binder = 96.8:0.2:3, apply it on the PRT membrane and test the resistivity of the membrane.
[0171] Viscosity change data test method: Place the conductive paste in a 25°C constant temperature box, take it out after 1 day, and test the viscosity of the conductive paste.
[0172] The rheological data, film resistance and viscosity change data of the conductive pastes in Examples 6 to 8 and Comparative Examples 1 to 2 measured according to the above test method are as follows: Figures 21 to 23 As shown. Fig.21 It can be seen that the rheological properties of the conductive pastes of Examples 6 to 8 are better than those of Comparative Examples 1 to 2. Fig. 22 It can be seen that the resistivity of the conductive pastes in Examples 6 to 8 is less than 200Ω·m, while the resistivity of the conductive pastes in Comparative Examples 1 to 2 is greater than 200Ω·m, indicating that the film resistance of the conductive pastes in Examples 6 to 8 is significantly lower than that in Comparative Examples 1 to 2. Fig.23 It can be seen that the viscosity change of the conductive pastes of Examples 6 to 8 after standing for 15 days is <500 cp, while the viscosity change of the conductive pastes of Comparative Examples 1 to 2 after standing for 15 days is >2000 cp.
[0173] In summary, the conductive paste in the present invention has excellent viscosity, fineness stability, excellent fluidity and leveling performance, no precipitation and stratification occurs after storage for 48 hours, the 7-day room temperature static viscosity change of the conductive paste is ≤2000cp, the 7-day room temperature static particle size change of the conductive paste is ≤1μm, the 7-day static fluidity of the conductive paste does not deteriorate, and the 7-day high-temperature static viscosity change of the conductive paste is ≤2000cp; in addition, the water-soluble dispersant in the conductive paste of the present invention can stably disperse the conductive agent, improve the stability of the conductive paste, further promote the construction of a three-dimensional conductive network, and reduce the resistivity.
[0174] The above is a detailed description of the embodiments of the present invention, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.
Claims
1. A water-soluble dispersant, characterized in that: Including polymers represented by formula (I): in, R + selected from H + , Na + , Li + , K + ; a is a natural number selected from 20 to 100; b is a natural number selected from 5 to 50.
2. The water-soluble dispersant according to claim 1, characterized in that: a is greater than b; And / or, the relative molecular mass of the polymer is 2600 to 15000; And / or, the solubility of the polymer in water at 25° C. is not less than 35 g / 100 g.
3. The method for preparing a water-soluble dispersant according to any one of claims 1 to 2, characterized in that: The following steps are involved: S1: mixing acrylic acid, a chain transfer agent and an initiator to carry out polymerization reaction to obtain a prepolymer; S2: The prepolymer, acrylonitrile and initiator are mixed to carry out polymerization reaction, and then mixed with water or alkaline solution to purify to obtain the water-soluble dispersant.
4. The method for preparing a water-soluble dispersant according to claim 3, characterized in that: The chain transfer agent is selected from At least one of .
5. A conductive paste, characterized in that: The invention comprises a conductive agent and the water-soluble dispersant according to any one of claims 1 to 2.
6. The conductive paste according to claim 5, characterized in that: The conductive paste comprises the following components in parts by weight: 0.2 to 10 parts of a water-soluble dispersant, 0.4 to 5 parts of a conductive agent, and 85 to 105 parts of a solvent.
7. The conductive paste according to claim 5, characterized in that: The conductive agent is selected from at least one of multi-walled carbon nanotubes, few-walled carbon nanotubes and single-walled carbon nanotubes.
8. A negative electrode slurry for a lithium ion battery, characterized in that: The conductive paste comprises the conductive paste according to any one of claims 5 to 7.
9. The negative electrode slurry for lithium ion battery according to claim 8, characterized in that: The negative electrode slurry for lithium ion battery comprises the following components in parts by weight: 0.1 to 3 parts of conductive slurry, 85 to 95 parts of active material, 1 to 5 parts of binder, and 30 to 85 parts of solvent.
10. Use of the water-soluble dispersant according to any one of claims 1 to 2 and / or the conductive paste according to any one of claims 5 to 7 in the field of batteries.